Total reuse of brewer’s spent grain in chemical and biotechnological processes for the production of added-value compounds - Mussatto, Solange I. (2008)
Brewer’s spent grain was fractionated by means of three different procedures: dilute acid hydrolysis, for the hemicellulose recovery; alkaline hydrolysis, for the lignin solubilization, and enzymatic hydrolysis, for the cellulose conversion into glucose. The best hydrolysis conditions were optimized to each case. The cellulosic and hemicellulosic hydrolysates produced under these conditions were used as fermentation medium for the production of lactic acid and xylitol, respectively. The efficiency of hemicellulose acid hydrolysis was >85% for all the evaluated conditions, but xylitol production was highest (0.70 g/g xylose) when the hydrolysate was obtained at 120 ºC, 17 min, using 1:8 g:g solid:liquid ratio, and 100 mg H2SO4/g dry matter. The best alkaline hydrolysis condition (120 ºC, 90 min, 2% w/v NaOH, 1:20 g:g solid:liquid ratio) gave a pulp constituted by 90.4% (w/w) cellulose, and a liquor containing several phenolic acids, mainly ferulic and p-coumaric. In the optimum condition of cellulose enzymatic hydrolysis (45 FPU/g dry matter, 100 rpm, 2% w/v substrate, 45 ºC, 96 h), cellulose was converted into glucose with 93.1% efficiency, and lactic acid was produced with high yield (0.98 g/g glucose) from this hydrolysate.